2023
DOI: 10.3390/foods12152933
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Genetically Modified Food Products and Its Determinants (Case Study: Edible Oil in Mashhad)

Reihaneh Zhaleh,
Hosein Mohammadi,
Flavio Boccia
et al.

Abstract: In recent decades, the global increase in the demand for food and the increasing growth of the world population has caused an inevitable transition from traditional to advanced agriculture and the use of new technologies in the production of food and agricultural products. One of the new achievements of biotechnology is the production and use of genetically modified plants. The benefits of genetically modified crops can be seen well beyond the farm as well, from helping to conserve natural resources to fightin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…This difference could primarily be attributed to the genetic factors of these oleaginous plants regarding their ability to produce oil. [ 27 ] The results indicated that the oil yield of spent coffee grounds was 17.19%. Similar findings were reported by Bijla et al., [ 28 ] who mentioned that the yield oil of spent coffee grounds varies from 8% to 18%.…”
Section: Resultsmentioning
confidence: 99%
“…This difference could primarily be attributed to the genetic factors of these oleaginous plants regarding their ability to produce oil. [ 27 ] The results indicated that the oil yield of spent coffee grounds was 17.19%. Similar findings were reported by Bijla et al., [ 28 ] who mentioned that the yield oil of spent coffee grounds varies from 8% to 18%.…”
Section: Resultsmentioning
confidence: 99%